Coordination of hamstrings is individual specific and is related to motor performance - Avrillon, S.; Guilhem, G.; Barthelemy, A.; Hug, F. (Journal of Applied Physiology, 2018)
The torque-sharing strategies between synergistic muscles may have important functional consequences. This study involved two experiments. The first experiment (n = 22) aimed 1) to determine the relationship between the distribution of activation and the distribution of torque-generating capacity among the heads of the hamstring, and 2) to describe individual torque-sharing strategies and to determine whether these strategies are similar between legs. The second experiment (n = 35) aimed to determine whether the distribution of activation between the muscle heads affects endurance performance during a sustained submaximal knee flexion task. Surface electromyography (EMG) was recorded from biceps femoris (BF), semimembranosus (SM), and semitendinosus (ST) during submaximal isometric knee flexions. Torque-generating capacity was estimated by measuring muscle volume, fascicle length, pennation angle, and moment arm. The product of the normalized EMG amplitude and the torque-generating capacity was used as an index of muscle torque. The distributions of muscle activation and of torque-generating capacity were not correlated significantly (all P > 0.18). Thus, there was a torque imbalance between the muscle heads (ST torque > BF and SM torque; P < 0.001), the magnitude of which varied greatly between participants. A significant negative correlation was observed between the imbalance of activation across the hamstring muscles and the time to exhaustion (P < 0.001); i.e., the larger the imbalance of activation across muscles, the lower the muscle endurance performance. Torque-sharing strategies between the heads of the hamstrings are individual specific and related to muscle endurance performance. Whether these individual strategies play a role in hamstring injury remains to be determined. NEW & NOTEWORTHY The distribution of activation among the heads of the hamstring is not related to the distribution of torque-generating capacity. The torque-sharing strategies within hamstring muscles vary greatly between individuals but are similar between legs. Hamstring coordination affects endurance performance; i.e., the larger the imbalance of activation across the muscle heads, the lower the muscle endurance.